ANALISIS DAMPAK PENGGUNAAN CRYPTOCURRENCY TERHADAP PERTUMBUHAN EKONOMI ISLAM DI INDONESIA - Nafia, Nala Ilma; Adinugraha, Hendri Hermawan (Al-Qashdu : Jurnal Ekonomi dan Keuangan Syariah, 2024)
This research aims to gain a better understanding of cryptocurrencies, including their working mechanisms and impact in economic and investment contexts. Apart from that, this research also wants to evaluate the potential consequences of the government’s lack of seriousness regarding the spread of cryptocurrency in Indonesia. The method used is a qualitative descriptive approach with normative aspects, including risk analysis and potential profits from investing in cryptocurrency. This research covers the spread of cryptocurrencies across Indonesia and the risks associated with their use. It is hoped that the results of this research will provide a deeper understanding of how cryptocurrencies work, their impact, and the role of governments in regulating their spread. Therefore, this research will provide important information for the government and society in making decisions regarding the regulation and use of cryptocurrency in Indonesia.Keywords: Cryptocurrency; Investment; Islamic Economics